Mass Media and its Impact on Building the Mental Image of the Iraqi Public, Rituals of Husseini as a Model - Mohammed ALI, Hussein Saadi (lark, 2021)
It is the responsibility of the Iraqi media to paint a picture for the recipient regarding the religious rituals associated with some ritual practices.  It is more necessary in light of the current situation in which the country is living, as it that to benefit from the noble values and principles that the Islamic religion has advocated and established.  And to achieve the strategic goal that Islam stipulated, it is imperative to secure a media capability in spreading a moderate thought befitting of the representation of Islam that appeared to the world with the emergence of the noble prophetic message and its continued spreading of light among all of humanity. The responsibility rests on the modern media system, which is keen to establish authentic religious concepts; it should not be without thoughtful media planning processes. This research came to shed light on the media’s potential to create perceptions of religious ritual practices with ideological affiliations among the Iraqi public. This research consists of three chapters. The first chapter addressed the Introduction of research (that represented the problem, the importance and the goals that this research seeks to achieve). While the second chapter included under the theoretical framework of the research, and the third topic focused on data analyzy , which is done through the extract results  of a quantitative method, and then the conclusions.